2020
DOI: 10.33541/jet.v6i2.47
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Students’ Perceptions on their Identity as Future EFL Teachers

Abstract: To be professional EFL teachers in the future, pre-service teachers should continuously construct their identities amid various obstacles and difficulties they confront in their working circumstances. This study attempted to investigate undergraduate students’ perceptions of their identity as future teachers. One research problem was proposed in this study namely: What are the factors influencing pre-service teachers to develop their teacher identity through Micro Teaching Class? This study applied qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(24 reference statements)
0
2
0
1
Order By: Relevance
“…In English teacher education contexts, the micro-teaching course is mainly intended to enhance the students' ability to teach so that they are ready to deal with the realities of the classroom. Therefore, this course will nurture their competency as future teachers (Mbato, 2020). The micro-teaching practice is useful for teacher candidates to reduce their deficiency in teaching skills and help them to develop much more positive attitudes towards their future profession (Sarıçoban, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In English teacher education contexts, the micro-teaching course is mainly intended to enhance the students' ability to teach so that they are ready to deal with the realities of the classroom. Therefore, this course will nurture their competency as future teachers (Mbato, 2020). The micro-teaching practice is useful for teacher candidates to reduce their deficiency in teaching skills and help them to develop much more positive attitudes towards their future profession (Sarıçoban, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Wijaya (2021) highly recommended that Indonesian EFL teachers progressively transform into more resilient educators amidst the taxing educational obstacles they are currently confronting as they channel their energy, commitment, and endeavor to their teaching vocation. Mbato and Wijaya (2020) strongly advocated for pre-service Indonesian EFL teachers to establish, nurture, and reinforce their genuine identities as compassionate educators to enable them to become agents of change willing to advance all educational qualities. Yumarnamto (2019) found that a vast majority of Indonesian EFL teachers could continually promote a more positively-sound learning atmosphere where all learners' target language competencies can be fostered to the utmost level as extensive moral support and supportive working climates are imparted by their educational institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Anderson (2019); respecto al buen manejo de competencias blandasMartin (2019) las menciona como importantes lo mismo queHaddad & Marx (2018); por su parteDonia, O'Neill & Brutus (2018) mencionan la importancia del dominio del trabajo en equipo junto conVogler et al (2018); ademásFrancis et al (2018) especifican la importancia del apoyo y soporte, en sus circunstancias, para su familia lo que confirmanSpengler et al (2018); la capacidad de asimilar errores y trascender lo mencionan Gamble & Crouse (2020) así como Russell, Smith, & Larsen (2020) que especifican este elemento como parte del éxito de los estudiantes; también la buena vocación profesional resulta interesante en los universitarios como lo estudianStebleton & Diamond (2018) yMbato & Wijaya (2020) como parte del éxito integral de los mismos; por último los jóvenes deben manifestar una mejora en sus relaciones intrapersonales,Henry & Thorsen (2018) lo menciona con aspectos como la empatía y buenas amistades, mientras que Morina (2019) lo lleva al punto de las relaciones de pareja como parte de las emociones y motivaciones de los estudiantes.Referente a las características personales del docente Burnham, Le & Piedmont (…”
unclassified